“If You Don’t Know Who They Are, You Don’t Know How to Support Them”: A Qualitative Study Exploring How Educators Perceive and Support Canadian Military-Connected Students - Hill, Shannon; Lee, Elizabeth A.; Cramm, Heidi (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
To date, American research has provided the foundation for what is known about the educational experiences of students living in military families. Given contextual differences that exist between the United States and Canada, it is unclear how representative the American findings are of the Canadian experience. Using semi-structured interviews, this phenomenological study collected data from six educators to better understand how the needs of military-connected students are addressed within Canadian secondary schools. Participants generally had a good understanding of the military lifestyle and its associated challenges for students. However, many participants were unaware of any formal mechanisms used to identify military-connected students, any professional development opportunities for educators, or any collaborations that exist between schools and the military to support such students. Given the current lack of Canadian research, this study will help contribute to the building of knowledge and capacity in the Canadian context.